Evaluation of Physical Exercise Program of Table Tennis Club in Bengkulu City - Al Ilham; Muhammad Faisal Lutfi Amri; Juni Isnanto; Sulasikin Sahdi Kadir (Al-Makki Publisher, 2023)
The problem in this study is that athletes always experience fatigue when competing in national events, it is due to their poor physical condition. The purpose in this study was to evaluate the physical exercise program of table tennis club coaching. This research was conducted at a table tennis club in the city of Bengkulu. This type of research is qualitative research with the CIPP method through a qualitative approach. CIPP consists of four stages, namely: Context, Input, Process, Product. Data were obtained through observation, questionnaires, interviews and documentation studies. This study uses non-statistical qualitative analysis methods, where the components of data reduction, and data presentation are carried out simultaneously with the data collection process after being collected, the three components analyzed (data reduction, data presentation, conclusions) interact. The results of this study show that (1) The process of eligibility mechanism and qualification of table tennis club coaches and athletes in Bengkulu City includes PTM. Rook, PTM. Post, PTM. Tebeng is already classified as decent. (2) The implementation of the physical training program has not gone well, in the sector of coaches and athletes. (3) The facilities and infrastructure owned by table tennis clubs in Bengkulu City are still categorized as not good because they are only PTM. Posts that have adjusted facilities and infrastructure according to PTMSI standards while PTM. Fortress and PTM. Tebeng still needs to be fixed.